The use of ultrasound in the assessment of the glenoid labrum of the glenohumeral joint. Part II: Examples of labral pathologies - Krzyżanowski, Wojciech (J Ultrason, 2012)
Labral pathologies of the glenohumeral joint are most commonly caused by trauma. The majority of lesions affect the anterior part of labrum, resulting from much higher frequency of anterior shoulder dislocations over posterior ones. Another subgroup of labral lesions, not directly related to joint instability, are SLAP tears. Other findings include degenerative changes of labrum and paralabral cysts. Diagnostic imaging is crucial for making a decision regarding operative treatment. Apart from a standard X-ray examination, the imaging mainly relies on magnetic resonance or computed tomography arthrography. Based on their own experience, the authors propose the use of ultrasound in the assessment of labral tears of the glenohumeral joint. Different signs indicating labral pathology may be discovered and assessed during ultrasound examination. They include permanent displacement of the labrum onto the glenoid, labral instability during dynamic examination, lack of the labrum in the anatomical position, hypoechoic zone at the base of the labrum >2 mm in width, residual or swollen labrum as well as paralabral cyst(s). The most frequent appearance of labral pathology is displacement of the anteroinferior labrum onto the external aspect of the glenoid typically seen after anterior shoulder dislocation. The another most important US feature is labral instability while dynamically examined. The swelling or reduced size of the labrum usually indicates degeneration. This article presents sonographic images of selected labral pathologies.